A Framework for Ontology-based Model of Information Management Assessment Criteria based on Syariah Compliance - Abdul Wahab, A.H.; Fauziah Abdul Wahid (Universiti Sains Islam Malaysia, 2024)
The Holy Quran and Hadith ontology models are gaining popularity among researchers due to people's demands in understanding these divine books. Due to this, there are many studies have been conducted in this area to facilitate people's understanding of the Quran and Hadith. From the literature, however, most existing Quran and Hadith applications cover either Quran or Hadith only. Some applications focus on a domain of knowledge, while others only apply term matching and do not provide a semantic interpretation of keyword for a query. Thus, the purpose of this paper is to propose a Quran and Hadith application that covers both prime reference sources in Islam. It will focus on one domain of knowledge that is information management assessment criteria, where there is still a lack of research in this domain. It will also apply the semantic interpretation of the keyword to obtain results that are more comprehensive related to the context of the keyword. Evidence from the Quran and Hadith (Sahih Bukhari) related to the criteria of information management assessment will also be provided. The expected outcome for this paper is a framework of an ontology-based model for information management assessment criteria based on Syariah compliance that will be a useful guide for Muslims and all to assess their daily routine of managing information whether it complies with Islamic rules or vice versa.